Image_1_Effects of Vitamin D2 (Ergocalciferol) and D3 (Cholecalciferol) on Atlantic Salmon (Salmo salar) Primary Macrophage Immune Response to Aeromonas salmonicida subsp. salmonicida Infection.pdf - Manuel Soto-Dávila; Katherinne Valderrama; Sabrina M. Inkpen; Jennifer R. Hall; Matthew L. Rise; Javier Santander (2020)
Vitamin D 2 (ergocalciferol) and vitamin D 3 (cholecalciferol) are fat-soluble secosteroid hormones obtained from plant and animal sources, respectively. Fish incorporates vitamin D 2 and D 3 through the diet. In mammals, vitamin D forms are involved in mineral metabolism, cell growth, tissue differentiation, and antibacterial immune response. Vitamin D is an essential nutrient in aquafeeds for finfish. However, the influence of vitamin D on fish cell immunity has not yet been explored. Here, we examined the effects of vitamin D 2 and vitamin D 3 on Salmo salar primary macrophage immune response to A. salmonicida subspecies salmonicida infection under in vitro conditions. We determined that high concentrations of vitamin D 2 (100,000 ng/ml) and D 3 (10,000 ng/ml) affect the growth of A. salmonicida and decrease the viability of S. salar primary macrophages. In addition, we determined that primary macrophages pre-treated with a biologically relevant concentration of vitamin D 3 for 24 h showed a decrease of A. salmonicida infection. In contrast, vitamin D 2 did not influence the antibacterial activity of the S. salar macrophages infected with A. salmonicida. Vitamin D 2 and D 3 did not influence the expression of canonical genes related to innate immune response. On the other hand, we found that A. salmonicida up-regulated the expression of several canonical genes and suppressed the expression of leukocyte-derived chemotaxin 2 (lect-2) gene, involved in neutrophil recruitment. Primary macrophages pre-treated for 24 h with vitamin D 3 counteracted this immune suppression and up-regulated the transcription of lect-2. Our results suggest that vitamin D 3 affects A. salmonicida attachment to the S. salar primary macrophages, and as a consequence, the A. salmonicida invasion decreased. Moreover, our study shows that the positive effects of vitamin D 3 on fish cell immunity seem to be related to the lect-2 innate immunity mechanisms. We did not identify positive effects of vitamin D 2 on fish cell immunity. In ...